Substitusi tepung tulang ikan tongkol (Euthynnus affinis) sebagai ingredient pangan pada pembuatan crackers roll tinggi kalsium: Substitution of tuna fish bone flour (Euthynnus affinis) as a food ingredient in the production of high calcium crackers roll - Alim, Najwa Saidah Cantika; Haryati, Sakinah; Aditia, Rifki Prayoga (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Tuna bone flour is a waste product of fish meatball processing which is rich in calcium and has the potential to be used as a food substitute ingredient. An ingredient is a material or component used in making food products for a specific purpose, such as providing taste, texture, or nutritional content. Crackers roll was chosen as a substitution medium because it is a snack that is popular with teenagers, so it can be an alternative to increase calcium intake which is still low among Indonesian teenagers. This study aims to determine the best concentration of tuna bone flour substitution and the characteristics of crackers roll. The data analysis method used in chemical and physical parameters used a Completely Randomized Design (CRD) with ANOVA, organoleptic tests using a hedonic scale on a scale of 1–9 followed by the Kruskal-Wallis and Whitney U tests, and the best product treatment using the DeGarmo method. The results showed that the best crackers roll was produced from a 5% substitution of tuna bone flour, with a hedonic value of appearance of 5.93, aroma of 5.93, taste of 5.27, and texture of 6.13. The chemical content includes water content of 5.35%, ash 7.21%, protein 11.8%, fat 23.4%, carbohydrate 52.10%, calcium 479.11 mg/100 g and hardness 2823.3 gf. With these contents, this product has met the criteria as a high calcium food and has the potential to become a functional food innovation that is nutritious and has a selling value.